Status Keberlanjutan Dimensi Ekologi Kemitraan Konservasi HHBK Kecombrang (Etlingera elatior) dan Pakis (Diplazium esculentum) Oleh BBTNKS dan KPPL Maju Bersama di Kawasan Hutan Madapi Provinsi Bengkulu - Wulansari, Pitri; Aprianto, Enggar; Susatya, Agus; Wiryono, Wiryono; Utama, Satria Putra (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2025)
The Conservation Partnership of Torch Ginger (Etlingera elatior) and Fern (Diplazium esculentum) by BBTNKS and the women's group concerned with the environment (KPPL) has been advancing together in the Madapi Forest Area Utilization Zone on an area of ​​10 Ha since 2019. The Ecological Study of the partnership was carried out so that activities can run according to the agreement stated in the cooperation agreement letter (SPKS). The purpose of this study was to determine the level of sustainability of Torch Ginger and Fern NTFP Management. This study uses a quantitative descriptive research method with Multidimensional scaling (MDS) analysis. The results of the study indicate that the sustainability status of the ecological dimension of the management of Torch Ginger Etlingera elatior and Diplazium esculentum fern in the Madapi Forest Utilization Zone of TNKS after the MDS analysis was carried out was in the sustainable category (76.88%> 75%) with an R2 value (94.52) and Strees 14.12%.